Partisipasi Orang Tua Dan Mutu Pendidikan Anak Sekolah di SD Muhammadiyah Metro Pusat Kota Metro Tahun Pelajaran 2017/2018 - Dwi Kartika Yanti (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2019)
This study aims to describe the role of school committees in supporting the improvement of the quality of education in Elementary School of Muhammadiyah Metro Center Metro City. This research uses qualitative method. The type of research is descriptive qualitative research. Subjects in the study were Principal, Vice Principal, School Committee. Data collection techniques used interviews, observation and documentation. The role of the school committee as a consideration, the role of school committees in raising funds, the role of school committees as supervisors, and the role of school committees in responding to complaints, criticism and aspirations of parents. The collected data is then analyzed using descriptive analysis technique. Data analysis comes from manuscripts, interviews, field notes, documentation and observation. The document is described so as to provide clarity to reality or reality. The results of research on the role of school committees in improving the quality of education management can be concluded that the school committee Elementary School of Muhammadiyah Metro Center can perform the role well. The role of the school committee as a consideration, the role of school committees in raising funds, the role of school committees as supervisors, and the role of school committees in responding to complaints, criticisms and parents' aspirations by school committees can support improving the quality of education.